Traditional Conflict Resolution Mechanism in Ethiopia - Million Esho Dezo (Britain International for Academic Research (BIAR-Publisher), 2021)
The study examines the role of Enashma traditional conflict resolution mechanism in handling conflict to maintain peace and stability. To realize the intended objectives, the study utilized case-study research approach with qualitative research method and the data were collected using observation, interview, focused-group discussion and document analysis. The data collected were analyzed and interpreted through word description and narration. According to the data obtained from the interview and focus group discussion, Enashma traditional conflict resolution mechanism has several advantages over the state law. Some of the advantages are restorative capacity, accessibility, revealing crime committed without witness and its acceptability. Paradoxically, the exclusion of women in the system, no standardized mechanism to fix payment of compensation for different conflicts, lack of supportive and strengthening measures from the government and lack of office for local elders are the major weakness of the institution as the information obtained from key informants. Therefore, the study recommended that all the stakeholders should be responsible tosolve the weakness of Enashma traditional conflict resolution mechanism in the study area.